1955
DOI: 10.1039/jr9550003871
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroalkyl derivatives of sulphur. Part III. Some reactions of trifluoromethanethiol, and spectroscopic properties of the 〉C:S group

Abstract: Haszeldiqze and K i d d .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
1

Year Published

1966
1966
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…Nucleophilic trifluoromethylthiolation was also investigated to introduce the trifluoromethanesulfenyl group. The low stability of trifluoromethylthiol and the corresponding anion represents one of the main challenges of such reactions 41. For example, the potassium trifluoromethylthiolate is in equilibrium with difluorothiophosgene and KF (Scheme ) 42,43…”
Section: The Historical Background Of Trifluoromethylthiolationmentioning
confidence: 99%
“…Nucleophilic trifluoromethylthiolation was also investigated to introduce the trifluoromethanesulfenyl group. The low stability of trifluoromethylthiol and the corresponding anion represents one of the main challenges of such reactions 41. For example, the potassium trifluoromethylthiolate is in equilibrium with difluorothiophosgene and KF (Scheme ) 42,43…”
Section: The Historical Background Of Trifluoromethylthiolationmentioning
confidence: 99%
“…The idea of this work came from the fact that trifluoromethylthiol and the corresponding anion are unstable. [9] It was reported that there is an equilibrium between trifluoromethanethiolate with carbonothioic difluoride and fluoride anion (Scheme 2 a). [10] Normally, the trifluoromethanethiolate is associated with a metal, such as Hg II , [11] Ag I , [12] or Cu I , [13] to stabilize the CF 3 S group.…”
mentioning
confidence: 99%
“…(1 7) (13,14)) wurden trotz rascher Entfarbung des Reaktionsgemisches (8 und 11 sind rot), nach mehr als 1 Woche Reaktionszeit noch Spuren der Ausgangsverbindung 1 a NMR-spektroskopisch nachgewiesen. Der Primiirkomplex 12 wird demnach rasch gebildet (Entfarbung), die Folgereaktionen durch Fluorid-und SCF3-Gruppen-Wanderung sind aber geschwindigkeitsbestimmend.…”
Section: \S 'unclassified